SOME DYNAMIC PROCESSES AT LONGITUDINALLY-TRANSVERSE SHIFT OF THE CARGO - Leontii MURADIAN; Anzhelika SHVETS; Angela SHVETS (Scientific Journal of Silesian University of Technology. Series Transport)
The purpose of the work is to study the influence of the longitudinally-transverse shift of the cargo’s center of mass on the dynamic loading of the wagon in order to solve the problem of predicting the dynamics and stability of an asymmetrically loaded railroad vehicle. During the analytical simulation, a multibody model of the spatial oscillations of the wagon was used. The differential equations of wagon oscillations are compiled using the d'Alembert principle, while the wagon is considered as a system with 42 degrees of freedom. The work presents the results of analytical simulation of some dynamic processes of interaction of railroad vehicles with the rails on the example of flat wagons. The results of the analytical simulation are presented, taking into account the speed of movement along the curved sections of the railway track. The proposed multibody model "heavy cargo – wagon" makes it possible to analytically determine the dynamic characteristics of the system and ensure the development of such methods of transportation of heavy cargo that meet the requirements of train traffic safety. The application of the obtained results will help improve the running safety of freight wagons and enhance the technical and economic performance of railways.